Brand Image Linkage, Product Diversity and Store Atmosphere to Customer Loyalty in Fashion Shops in Bali - Ribek, Pande Ketut; Purnawati, Ni Luh Gede Putu; Pendet, Ketut Muka; Yuliastuti, Ida Ayu Nyoman (Institut Seni Indonesia Denpasar, 2024)
Loyalty is created based on the experience of consumers buying and consuming products, the factors that influence the emergence of customer loyalty so that they can carry out the right strategy for the survival of the company. brand image, product variety, and store atmosphere. The purpose of this study was to analyze the effect of brand image, product variety, and store atmosphere on customer loyalty. The population of this study are consumers who come to shop at least 2 times. The sampling technique is purposive sampling, this method uses the census method with a total of 102 fashion shop owners. Samples in this study were 102 respondents, with multiple linear regression analysis. Results of this study brand image has a significant positive effect on customer loyalty, product variety has a significant positive effect on customer loyalty, store atmosphere has a significant positive effect on customer loyalty in fashion stores in Bali.